О ДВУХ МИНЕРАЛОГИЧЕСКИХ ТИПАХ РОССЫПНОГО ЗОЛОТА БАССЕЙНА РЕКИ ЧАРЫ - Тулаева Е.Г.; Никифорова З.С. (My University, 2006)
Basin of the Chara river, with two its main inflows - the Tokko and Torgo rivers, is generally characterized by the widespread background placer gold bearing. The gold is represented there mainly by lamella-shaped particles, with dominating faction of 0.1-0.25 mm and high fineness. These particles often have on the surface marks impressed by mineral grains; the sources of their placer accumulation arc connected with some intermediate poor-in-gold collectors in Paleozoic and Mesozoic sediments. Actually, for the first time, there was detected the second type of placer gold distinguished by primary or sub-primary habit of gold particles, their larger size - +0.25 mm, and lower fineness - 600-800 %o. This type of gold is probably connected with Achaean and Proterozoic faults activated in Mesozoic.
Keywords: 549.263